The Age of Responsibility: CSR 2.0 and the New DNA of Business - Visser , Wayne (Journal of Law and Governance, 2010)
This paper argues that CSR, as a business, governance and ethics system, has failed. This assumes that success or failure is measured in terms of the net impact (positive or negative) of business on society and the environment. The paper contends that a different kind of CSR is needed if we are to reverse the current direction of many of the world’s most pressing social, environmental and ethical trends. The first part of the paper reviews business’s historical progress over the Ages and Stages of CSR: moving through the Ages of Greed, Philanthropy, Marketing and Management, using defensive, charitable, promotional and strategic CSR approaches respectively. The second part of the paper examines the Three Curses of Modern CSR (incremental, peripheral and uneconomic), before exploring what CSR might look like in an emerging Age of Responsibility. This new CSR – called systemic or radical CSR, or CSR 2.0 – is based on five principles (creativity, scalability, responsiveness, glocality and circularity) and forms the basis for a new DNA model of responsible business, built around the four elements of value creation, good governance, societal contribution and environmental integrity.